全球石炭纪煤的分布规律 - 毛翔; 李江海 (煤炭学报, 2014)
石炭纪是全球第一个大量富集煤炭资源的时代,煤层广泛分布于北美、欧洲与亚洲,但同期烃源岩分布则十分有限.建立在系统地结合古地磁、区域地质、沉积盆地数据库和资料基础上,绘制的石炭纪全球古板块再造-古地理与岩相系列图件,有效地从地球系统的角度揭示了导致这一差异的原因.石炭纪时期,冰盖面积广阔、海平面下降、陆地大面积高出海面,植物繁盛;全球洋流整体表现为暖流自东向西移动,寒流自西向东移动,全球主要沉积作用发生在各大陆周缘及陆内浅海分布区;南北半球均发育热带、干旱带、温带与寒带,植物与气候出现对应的分布趋势.由于劳俄大陆、哈萨克斯坦板块、西伯利亚板块、华北板块等处于热带及北半球干旱带,属于热带全年潮湿植物区与温带植物区,有利的地理、植物特征造成煤广泛分布;而冈瓦纳大陆处于南半球较高纬度,且其中南部发育冰盖区,植物类型为寒带植物区,煤分布较少.海域面积减小、温度降低、大气中氧气含量突增导致的海水氧化增强,一系列不利条件导致全球石炭纪烃源岩仅占整个地质时代烃源岩总形成量的约8％. Carboniferous is the first time in the geological history that coal is largely distributed and concentrated in the North America, Europe and Asia, while the distribution of source rock is much less. Based on systematically combining recent paleomagnetism and regional geology with a database of sedimentary basins, a global Carboniferous paleoplate reconstruction-paleogeographic map, and a lithofacies map were drawn to reveal the global energy geological features. During the Carboniferous, there was a large ice sheet located in the southern hemisphere. The growth of the ice sheet led to descending sea levels, and as a result, vast areas of land were exposed across Laurasia and Gondwana, leading to abundant and thriving plant life. Warm ocean currents flowed from east to west, while colder currents flowed from west to east. The greatest amount of sedimentation occurred in the peripheries of the main continents and in the shallow seas located within the continents. Both the southern hemisphere and the northern hemisphere developed tropical zones, arid zones, temperate zones and frigid zones, and the flora Provinces had a similar distribution to the climate zone. Located in the tropical and arid zones of the northern hemisphere, The floral regions in Laurussia, kazakhstan plate, Siberian plate and North China plate belonged to tropical ever wet and warm temperate Provinces. Their climate and abundant flora were both well-suited for coal forming processes to take place. The Gondwana supercontinent was mainly located in the higher latitudes very close to the ice sheet, with flora representative of the cool temperate Province, where coal forming ceases. The regression of the seas, lower temperatures, and the increasing atmospheric oxygen levels, caused by the photosynthesis, led to an increase in the oxidation degree of the sea water. The combined effects of these factors made the amount of Carboniferous source rock very limited, which together accounted for 8% of the total source rock of the world. EI 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 0 z1 198-203 39